Collimation and Exposure Parameter Influence Image Quality and Potential Radiation Dose to the Eye Lens of Personnel in Computed Radiography of the Canine Pelvis - Bisgaard, Malene; McEvoy, Fintan J.; Nielsen, Dorte Hald; Allberg, Clara; Müller, Anna V.; Timm, Signe; Meyer, Signe N.; Johansen, Line Marie; Pedersen, Stine; Precht, Helle (Frontiers in Veterinary Science, 2021)
Introduction The purpose of this study was to evaluate the effect of collimation on image quality and radiation dose to the eye lenses of the restrainer involved in computed radiography of the canine pelvis. Materials and methods First, a retrospective study of canine pelvic radiographs (N=54) evaluated image quality related to the collimation field used. Second, a prospective cadaver study (N=18) assessed the effects on image quality and on scattered radiation dose, of different collimation field areas and exposure parameters. All radiographs were analyzed using a Visual Grading Analysis (VGA) with three observers. Third, the potential scattered radiation dose to the eye lens of personnel restraining a dog for pelvic radiographs was measured. Results The retrospective study showed a slightly better (statistically non-significant) VGA score for the radiographs with optimal collimation. Spatial-, contrast resolution and sharpness increased the visualized image quality the most when minimizing the collimation field. The prospective study showed slightly better VGA scores with the optimal collimation. Increasing the exposure factors especially mAs, the better low contrast resolution and less noise was visualized in the radiographs. The potential eye lens radiation dose increased by 14%, 28% and 40% (default, increased kV, increased mAs, respectively) between optimal and extended collimation. Conclusion Collimation size slightly influences image quality and clearly has an impact on scattered radiation to the personnel in the X-ray room. With regard to radiation safety, increases in kV are associated with less potential scatter radiation exposure compared to comparable increases in mAs.